Regulation of genes encoding enzymes involved in plant cell wall deconstruction in Trichoderma reesei - Ries, Laure Nicolas Annick (2013)
This study describes the regulation of genes encoding plant cell wall-degrading enzymes in the presence of different carbon sources from the biotechnologically important fungus Trichoderma reesei. It was shown that different carbon sources influence fungal growth rate, biomass production and subsequent enzyme secretion. Several genes were identified and suggested to play a role in the development of conidia and in maintaining polarised growth. RNA-sequencing studies showed an increase in transcript levels of genes encoding enzymes involved in plant cell wall degradation (CAZy) as well as of genes encoding lipases, expansins, hydrophobins, G-protein coupled receptors and transporters when mycelia were cultivated in the presence of a lignocellulosic substrate (wheat straw). The encoded non-CAZy proteins were proposed to have accessory roles in carbohydrate deconstruction. A model for solid substrate recognition in T. reesei was described, based on the comparison with the one proposed for Aspergillus niger. Post-transcriptional regulation mediated by regulatory RNAs was identified for nearly 2% of all T. reesei genes, including genes encoding cell wall-degrading enzymes. Transcriptional regulation studies confirmed that transcription patterns of genes encoding enzymes involved in polysaccharide degradation differed between different carbon sources and that they are fine-tuned and dependent on factors such as culture conditions, consumption rate, assimilation of glucose and the presence of several transcription factors. The analysis of the structure of chromatin in the promoter and coding regions of one of these genes, cbh1, revealed different nucleosome positioning patterns under repressing (glucose) and inducing (sophorose, cellulose) conditions. CRE1, the carbon catabolite repressor in T. reesei was shown to be involved in the repression of many CAZy and non-CAZy encoding genes. Furthermore, CRE1 was also shown to be important for nucleosome positioning within the cbh1 coding region under repressing conditions and proposed to do so by interaction with (a) yet unidentified protein(s).